Regional Economic Outlook, October 2018, Europe : Domestic Expansion Running into External Turbulence. (Regional Economic Outlook, 2018)
Economic activity continued to expand in the first half of 2018, albeit at a slower-than-expected pace, mainly in advanced Europe. Domestic demand, supported by stronger employment and wages, remains the main engine of growth. However, the external environment has become less supportive and is expected to soften further in 2019 owing to slowing global demand, trade tensions, and higher energy prices. Tighter financial conditions in vulnerable emerging market economies and maturing business cycles are also weighing on activity. Accordingly, growth is projected to moderate from 2.8 percent in 2017 to 2.3 percent in 2018 and 1.9 percent in 2019. That said, it is expected to remain above potential in most countries in the region.